2021
DOI: 10.1016/j.bioactmat.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated degradation of HAP/PLLA bone scaffold by PGA blending facilitates bioactivity and osteoconductivity

Abstract: The incorporation of hydroxyapatite (HAP) into poly- l -lactic acid (PLLA) matrix serving as bone scaffold is expected to exhibit bioactivity and osteoconductivity to those of the living bone. While too low degradation rate of HAP/PLLA scaffold hinders the activity because the embedded HAP in the PLLA matrix is difficult to contact and exchange ions with body fluid. In this study, biodegradable polymer poly (glycolic acid) (PGA) was blended into the HAP/PLLA scaffold fabricated by laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(151 citation statements)
references
References 58 publications
5
146
0
Order By: Relevance
“…And the blend of biodegradable polymer PGA could make the scaffold exhibit tunable biodegradability which facilitated the exposure of HA during the degradation process. It's confirmed that this scaffold displayed desirable cytocompatibility in vitro and excellent bone repair capacity in vivo [ 271 ]. Feng et al incorporated biodegradable polymer PLLA into Polyetheretherketone (PEEK)/β-TCP scaffold to facilitate the exposure of β-TCP during scaffold degradation.…”
Section: Natural Bone-healing Process and Mechanismmentioning
confidence: 85%
“…And the blend of biodegradable polymer PGA could make the scaffold exhibit tunable biodegradability which facilitated the exposure of HA during the degradation process. It's confirmed that this scaffold displayed desirable cytocompatibility in vitro and excellent bone repair capacity in vivo [ 271 ]. Feng et al incorporated biodegradable polymer PLLA into Polyetheretherketone (PEEK)/β-TCP scaffold to facilitate the exposure of β-TCP during scaffold degradation.…”
Section: Natural Bone-healing Process and Mechanismmentioning
confidence: 85%
“…We have still reported the grafting of ARX with acrylic acid (AAc) as there is relative research available on ARX- co -AAc. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Biocomposites can result from the polymer-ceramic bonding of calcium phosphate (HA or TCP) or bioactive polymer-glass, facilitating cell adhesion and proliferation [ 20 , 32 ] and, as a result, bone regeneration/reparation [ 15 ]. In this regard, it has recently been reported that the incorporation of hydroxyapatite (HAP) into a biodegradable polymer (i.e., poly l-lactic acid) (PLLA) matrix exhibit bioactivity and osteoconductivity showing excellent bone defect repair capacity with the formation of abundant new bone tissue and blood vessel tissue [ 53 ]. Moreover, authors such as Gendviliene I [ 18 ] proved that biocomposites achieved higher printing accuracy than pure polymers.…”
Section: Resultsmentioning
confidence: 99%